Pelatihan Pembuatan Tasima (Produk Olahan Singkong) dan Pengukuran LiLA untuk Mencegah Kejadian Ibu KEK - Zaenal Fanani; Septiani Septiani; Irawati Indrianingrum (Universitas Muhammadiyah Mataram, 2026)
Abstract: Cassava agricultural products have been sold as raw materials for the cassava processed product industry. The community in Singorojo Village has not been able to produce processed foods from cassava, which could be a superior product for the region. Cassava can be part of the Supplemental Feeding (PMT) for pregnant women experiencing KEK because its nutritional content can help meet energy and nutritional needs. The purpose of this activity is for early detection of mothers at risk of KEK by measuring the Upper Arm Circumference (LILA), as well as appropriate nutritional interventions in the event of KEK by consuming Tasima, a high-calorie cassava processed product. This community service is focused on providing solutions to partner problems, especially in the health and food aspects. An overview of technology and innovation is implemented through health education about the nutritional content and benefits of cassava. Training on LiLA measurement applications, and training on making Tasima. The results of the community service are in the form of procurement of LiLA measurement tools, so that it can improve health services for the prevention of KEK mothers. Furthermore, increased Tasima production, so that it is more widely known to the community and provides positive feedback for additional nutritious food. The Singorojo community utilizes social media to reach a wider consumer base, increase sales, and diversify family income sources.Abstrak: Hasil pertanian singkong selama ini dijual sebagai bahan baku industri produk olahan singkong. Masyarakat di Desa Singorojo belum dapat memproduksi makanan olahan dari singkong, yang bisa dijadikan produk unggulan daerah tersebut. Singkong dapat menjadi bagian Pemberian Makanan Tambahan (PMT) untuk ibu hamil yang mengalami KEK karena kandungan nutrisinya dapat membantu memenuhi kebutuhan energi dan gizi. Tujuan kegiatan ini adalah untuk deteksi dini Ibu yang berisiko KEK dengan pengukuran Lingkar Lengan Atas (LiLA), serta intervensi gizi yang tepat pada kejadian KEK dengan konsumsi Tasima produk olahan singkong tinggi kalori. Pengabdian ini difokuskan untuk memberikan solusi dari permasalahan mitra, khususnya pada aspek kesehatan dan pangan. Gambaran teknologi dan inovasi diimplementasikan melalui edukasi kesehatan tentang kandungan nutrisi dan manfaat singkong. Pelatihan aplikasi pengukuran LiLA, serta pelatihan pembuatan Tasima. Hasil pengabdian berupa pengadaan alat pengukuran LiLA, sehingga dapat meningkatan pelayanan bidang kesehatan untuk pencegahan kejadian Ibu KEK. Selanjutnya peningkatan produksi Tasima, sehingga lebih banyak dikenal masyarakat dan memberikan feedback positif untuk tambahan makanan bergizi. Masyarakat Singorojo memanfaatkan media sosial, untuk menjangkau konsumen yang lebih luas, meningkatkan penjualan, dan mendiversifikasi sumber pendapatan keluarga.